Relative effectiveness of four types of informational material to PACD adult classes in some Laguna barrios - Gomez, Ely D. 1934- ([Quezon City s.n.], 1964)
The purpose of this study is to find out which among four types of informational material: 1) technical, 2) semi-technical, 3) popular, non-illustrated, and 4) popular, semi-illustrated, is most effective in presenting informational material to the Presidential Assistant on Community Development (PACD) adult classes.
Thesis (M.Ed.)--University of the Philippines
Keywords: Philippines (Republic) -- Presidential Assistant on Community Development; Education of adults